2003
DOI: 10.1046/j.1444-2906.2003.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal gelation of salted paste from scallop striated adductor muscle

Abstract: Salted muscle paste containing 60–100 mg protein/g paste and 0.5 M NaCl at pH 7.0 was prepared from fresh scallop striated adductor muscle and its heat‐induced gelling characteristics were examined in order to produce invertebrate kamaboko‐like foods. The heating of the paste to 90°C formed a weak gel. The setting effect on the gelation of the paste was introduced by incubation at 25°C for up to 4 h and was greatly strengthened by the addition of 10 mM Ca2+ due to the activation of an endogenous transglutamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…This characteristic increase in G′′ is caused by the presence of paramyosin, which comprises 16–18% squid muscle proteins, 19 as described previously 3 . The typical increase in G′′ also demonstrates the thermal gelling process of paramyosin, which was isolated from scallop adductor smooth muscle in a temperature range of 48–65°C 20 …”
Section: Resultssupporting
confidence: 66%
“…This characteristic increase in G′′ is caused by the presence of paramyosin, which comprises 16–18% squid muscle proteins, 19 as described previously 3 . The typical increase in G′′ also demonstrates the thermal gelling process of paramyosin, which was isolated from scallop adductor smooth muscle in a temperature range of 48–65°C 20 …”
Section: Resultssupporting
confidence: 66%
“…As expected, CaCl 2 significantly increased hardness and WHC of gels ( P < 0.05). Our results agreed with the report that the breaking strength of salted‐muscle paste gels was greatly increased by the addition of 10 m m Ca 2+ (Yoshida et al. , 2003).…”
Section: Resultssupporting
confidence: 93%
“…Taskaya et al 25 reported no gelling ability of proteins recovered by the pH shift method from whole carp unless gel enhancers were added. In order to make comparisons with gels from other marine bivalve molluscs, one must go to studies on isolated green mussel ( Perna viridis ) actomyosin43 and paste from fresh scallop striated adductor muscle 51. Gels from both these materials were reported to have relatively weak gel‐forming ability as indicated by frequency sweep (i.e.…”
Section: Discussionmentioning
confidence: 99%